Auditory evoked potential: a proposal for further evaluation in children with learning disabilities - Frizzo, Ana C. F. [UNESP] (2015)
The information presented in this paper demonstrates the author's experience in previews cross-sectional studies conducted in Brazil, in comparison with the current literature. Over the last 10 years, auditory evoked potential (AEP) has been used in children with learning disabilities. This method is critical to analyze the quality of the processing in time and indicates the specific neural demands and circuits of the sensorial and cognitive process in this clinical population. Some studies with children with dyslexia and learning disabilities were shown here to illustrate the use of AEP in this population.